Approximation of (ψ, β)-differentiable functions by Poisson integrals in the uniform metric - Zhyhallo, T. V.; Kharkevych, Yu. I. (Ukrains’kyi Matematychnyi Zhurnal, 2009)
We obtain asymptotic equalities for upper bounds of approximations of functions from the class $C_{β,∞} ψ$ by Poisson integrals in the metric of the space $C$.